Forensic Autosomal Short Tandem Repeats and Their Potential Association With Phenotype - Wyner, Nicole; Barash, Mark; McNevin, Dennis (Frontiers in Genetics, 2020)
Forensic DNA profiling utilises short tandem repeat (STR) markers to establish identity of missing persons, confirm familial relations and link persons of interest to crime scenes. It is a widely accepted notion that genetic markers used in forensic applications are not predictive of phenotype. At present, there has been no demonstration of forensic STR variants directly causing or predicting disease. Such a demonstration would have many legal and ethical implications. For example, is there a duty to inform a DNA donor if a medical condition is discovered during routine analysis of their sample? In this review, we evaluate the possibility that forensic STRs could provide information beyond mere identity. An extensive search of the literature returned 107 articles associating a forensic STR with a trait. 57 of these studies met our inclusion criteria: a link between a STR‐inclusive gene and a phenotype and a statistical analysis reporting a p‐value less than 0.05. A total of 50 unique traits were associated with 24 markers included in the 57 studies. TH01 had the greatest number of associations with 27 traits reportedly linked to 40 different genotypes. Five of the articles associated TH01 with schizophrenia. None of the associations found were independently causative or predictive of disease. Regardless, the likelihood of identifying significant associations is increasing as the function of non‐coding STRs in gene expression is steadily revealed. It is recommended that regular reviews take place in order to remain aware of future studies that identify a functional role for any forensic STRs.